Modeling of the signal propagation in real systems with finite interval and absorption - Kryvonos, Yu. G.; Selezov, I. T. (Reports of the National Academy of Sciences of Ukraine, 2016)
The wave propagation is investigated on the basis of a generalized hyperbolic equation with dissipation describing the wave propagation with finite velocity. The propagation of harmonic waves and the initial boundary-value problem of a propagation of the pulse from the input on a finite interval with full absorption are analyzed on the basis of the Laplace transformation and a numerical inverse transformation.